Revisit the hospital policy in the era of COVID-19 - Piryani, Rano Mal; Piryani, Suneel; Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2020)
Patient with recent history of dry cough, fever and breathlessness (influenza-like or severe acute respiratory illness) without alternative explanation/diagnosis needs to be managed as COVID-19 unless proved otherwise. Suspected COVID-19 patient having fever and recent loss of taste and smell be tested for COVID-19. Patient with severe acute respiratory illness of unknown aetiology be tested for COVID-19. Patient with bilateral consolidation on chest X-ray or ground glass appearance on chest CT or interstitial oedema on chest ultrasound (not fully explained by volume overload) be tested for COVID-19 in moderate to high risk communities/countries. Suspected COVID-19 patients with lymphopenia, high ESR or rise in C-reactive protein and suspected of viral fevers be tested for COVID-19. Screening of pregnant women for COVID-19 with rapid testing preferably with Elisa in moderate to high risk communities/countries. Screening with rapid testing preferably with Elisa prior to invasive interventions, including operations, in moderate to high risk communities/countries. Limit the exposure of hospital staff who are susceptible to develop severe complications of COVID-19. Hospitals provide PPE to staff depending upon exposure as per international/national/local guidelines. Hospitals implement infection prevention control measures meticulously in context of COVID-19.